Sozialabbau im Namen der Generationengerechtigkeit? - Böhning, Björn; Burmeister, Kai (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2004)
During recent years a debate about violated justice between the generations has become a popular issue in the political discussion in almost all western societies. The often used label “generation justice” is used as a justification for a deconstruction of elements of social policy, especially in the fields of health insurance and public pensions. The main argument is due to a changing demographic structure, in which social systems are no longer able to guarantee high standard social services. This essay tries to critically asses the current debate about intergenerational justice and to focus at first on improved economic foundation for transfers between the different generations. In a second step it is asked, if generation justice is a relevant topic for young people in their ordinary lives. In a final third step the essay will try to give a solid answer to the demographic change, which can be the foundation for a new contract between younger and older people.